2009
DOI: 10.1177/1090198109335656
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Sensitivity to External Food Cues: How Distance to Serving Bowl Influences Children’s Consumption

Abstract: Overweight is increasing in children, leading to negative health consequences. Children also lack appropriate levels of important vitamins and nutrients in their diets. Environmental cues, such as food proximity, have been shown to influence consumption rates in adults. The present study has tested whether proximity to either a nutrient-dense or caloric-dense food would influence children's snack consumption in a day care setting. Children (N = 46, age range 3.4-11) consumed more of both nutrient- and energy-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 15 publications
3
33
0
Order By: Relevance
“…Most studies were undertaken within the home setting (thirty-seven exposures/strategies out of fifty-five), primarily in observation studies (thirty-one out of thirty-seven). The majority of research within educational institutions has been from intervention studies; seven strategies (3,39,46,54) were identified compared with two exposures from observational studies (53) . A total of six exposures have been examined within the community setting, all from observational research (26,27,29,41,48,51) .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies were undertaken within the home setting (thirty-seven exposures/strategies out of fifty-five), primarily in observation studies (thirty-one out of thirty-seven). The majority of research within educational institutions has been from intervention studies; seven strategies (3,39,46,54) were identified compared with two exposures from observational studies (53) . A total of six exposures have been examined within the community setting, all from observational research (26,27,29,41,48,51) .…”
Section: Resultsmentioning
confidence: 99%
“…1). Over half of studies were based in the USA (n 18) (2,3,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) or Australia (n 6) (41)(42)(43)(44)(45)(46) . Twenty-three were cross-sectional, observational studies (1,2,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(41)(42)(43)(47)(48)(49)(50)(51)(52)(53) (see online supplementary material, Supplementary Table 1), with an average sample size of 563 (range 41 (31) -2074 (50) ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations